A THIRD HARMONIC PROPAGATION MODEL FOR SALIENT POLE SYNCHRONOUS GENERATOR IN MEDIUM VOLTAGE SYSTEM - ABDULLAH, MOHO FARIS (2015)
Harmonics is one of the important category in power quality problem \1ajotity of literatures discuss on the harmonics caused by non-linear load and very few researchers study on harmonics originated from salient pole synchronous generator. The third harmonic current produced by salient pole synchronous generator has always been associated with high neutral current causing problem to neutral earthing resistor, telecommunication system, and earthfault protection. The phenomenon that third harmonic power flow in the opposite direction of fundamental frequency ignites the proposed third harmonic model for salient pole synchronous generator in medium voltage system. The main contribution of the research is the development of the third harmonic model using symmetrical component analysis under newly defined balanced system in third harmonic domain.